2010
DOI: 10.1007/s12558-010-0116-y
|View full text |Cite
|
Sign up to set email alerts
|

Carcinome épidermoïde de la tête et du cou dans une population ougandaise: étude épidémiologique descriptive

Abstract: Introduction: Head and neck squamous cell carcinoma is the seventh most frequent type of cancer in the world, but its prevalence in African countries is about twoto four-folds higher than the developed countries. Despite improved surgical technique, chemotherapeutic and radiation intervention, the mean five-year survival remains one of the lowest among the main cancers, thus justifying studies that contribute to the development of preventive strategies. Objectives: The aim of this study was to compare the epid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…This was consistent with other studies [21] but different from others [9, 11, 14]. The possibility of misclassification of original OSCC site is high given the complex anatomy of the oral cavity coupled with delayed presentation seen among our patients [22]. In advanced stages, there could be an overlap of oral tumours that arise from adjacent structures leading to misclassification.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with other studies [21] but different from others [9, 11, 14]. The possibility of misclassification of original OSCC site is high given the complex anatomy of the oral cavity coupled with delayed presentation seen among our patients [22]. In advanced stages, there could be an overlap of oral tumours that arise from adjacent structures leading to misclassification.…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to an earlier study done in Uganda so no change in age distribution [25]. As expected due to matching on age and gender, there was neither statistically significant difference between male and female distribution nor between HIV positive and negative patients as per age groups (P=0.09 χ 2 10.7 df 6) (p=0.97 χ 2 =1.23 df 6) respectively.…”
Section: Discussionsupporting
confidence: 89%
“…As expected due to matching on age and gender, there was neither statistically significant difference between male and female distribution nor between HIV positive and negative patients as per age groups (P=0.09 χ 2 10.7 df 6) (p=0.97 χ 2 =1.23 df 6) respectively. The combined male to female ratio was 1.7:1 in contrast with 1.3:1 in an earlier study [25] but close to what was reported from Egypt [26]. However, the ratio is lower than what has been reported from most developed countries [27].…”
Section: Discussionsupporting
confidence: 76%
“…The commonest histological type is squamous cell carcinoma (SCC) accounting for more than 90% of HNC [2]. Globally and locally, more than half of these cancers arise from the oral cavity/ oropharynx [1,3].…”
Section: Introductionmentioning
confidence: 99%